IN MODERN LINGUISTICS, SPEECH IS THE STRUCTURE AND USE OF LANGUAGE (Лучшие интеллектуальные исследования, 2025)
In modern linguistics, discourse refers to the structure and use of language beyond the level of the individual sentence, focusing on how language functions in communication and social contexts. While syntax and semantics typically deal with the form and meaning of isolated sentences, discourse analysis examines how these sentences work together to create meaning in larger stretches of language, such as conversations, written texts, and speeches.